Saut d'Eau [Island] and Pichon [Cove] from the Maracas Road, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, [Trinidad and Tobago], 2011)
The postcards shows Saut d'Eau Island and Pichon Cove located off the coast of Trinidad, below the Maracas North Coast Road. Pichon Cove is one on the beaches in the La Vache Bay. Saut d'Eau Island which is the only breeding ground for the brown pelican (Pelecanus occidentalis) was proclaimed a wildlife sanctuary in 1935. Postcard number J240.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Inlets--Trinidad and Tobago; Wildlife refuges--Trinidad and Tobago; Protected areas--Trinidad and Tobago; Animal sanctuaries--Trinidad and Tobago; Bird refuges--Trinidad and Tobago; Birds--Trinidad and Tobago; Brown pelican--Trinidad and Tobago; Coasts--Trinidad and Tobago; Trees--Trinidad and Tobago